THE MODEL OF CREATING TELEMEDICAL SYSTEM IN UZBEKISTAN AND ITS PROBLEMS (Scientific journal of the Fergana State University, 2023)
This article discusses various obstacles to the development of telemedicine in the Republic of Uzbekistan and developing countries, the problems and requirements for telecommunications systems in the organization of telemedicine, as well as the possible architecture of telemedicine in the Republic of Uzbekistan